PENGGUNAAN MATERIAL RAMAH LINGKUNGAN PADA BANGUNAN HIJAU: PERUMAHAN TAMAN ANGGREK - Rifkah, Rifkah (Universitas Muhammadiyah Palembang, 2024)
This study examines the use of environmentally friendly materials in green buildings, focusing on Taman Anggrek housing as a case study. Construction is a major contributor to carbon emissions, with significant impacts from material production, energy use, and waste generation. The green building concept emerges as a solution to reduce environmental impacts, emphasizing eco-friendly materials, energy efficiency, water management, and waste reduction. This research assesses the implementation of green building standards, particularly in the selection of materials such as locally sourced concrete and certified environmentally friendly cement, in line with Permen PUPR No. 21/2021. Using case studies and literature analysis, the study evaluates material choices and their sustainability impacts. Findings suggest that local sourcing and certified materials contribute to reducing the carbon footprint and enhancing long-term sustainability in subsidized housing. Challenges remain in fully aligning with sustainable practices, particularly in the use of renewable materials. The study underscores the role of eco-friendly materials in achieving sustainable green housing in developing countries.